Audiological tinnitus management: an essential audiological protocol for elderly patients with comorbidity of hypertension and tinnitus (2019)
Elderly population with comorbidity of hypertension and tinnitus is increasing across the world, and the dilemma in the management of such elderly patients across the neurology and audiology/otology clinics seems enormous due to the attendant effects of such health-related comorbid conditions and ageing. This has been observed to have negative effect on the general well-being of quite a number of the elderly patients identified with the comorbid health conditions. It has also increased the tinnitus severity and related psychosocial reactions of the elderly patients. Worse still, the situation causes undulating increase in the prevalence of the comorbid condition of advanced age both male and female irrespective of cultural differences. Due to the aforementioned, this chapter is written with the aim of highlighting the efficacy of audiological tinnitus management options considered essential in the rehabilitation of individuals with comorbidity of hypertension and tinnitus. The chapter also discusses the benefits of combined therapies in rehabilitating elderly patients with comorbidity of hypertension and tinnitus and concluded with some useful recommendations for effective management of the comorbid condition.